Empirical investigations of social space - Blasius, Jörg; Lebaron, Frédéric; Le Roux, Brigitte; Schmitz, Andreas (Methodos series, 2019)
Introduction (Jörg Blasius , Frédéric Lebaron, Brigitte Le Roux & Andreas Schmitz -- PART I: Construction of the Social Space -- Chapter 1. The Social Space as Matrix Concept (Loïc Wacquant) -- Chapter 2. At the Apex of Educational Capital: The Space of Secondary Education in the University Town of Uppsala (Ida Lidegran, Mikael Börjesson & Donald Broady) -- Chapter 3. Similarity in Form, Difference in Capital The Structure of the Swedish Social Space and the Role of Educational Capital, 1990–2008 (Andreas Melldahl) -- Chapter 4. A Place at what Table? An Analysis of Symbolic Capital Hierarchies at the Norwegian Central Bank’s Annual Dinner (Johs. Hjellbrekke & Olav Korsnes) -- Chapter 5. Changes of Lifestyles in the Social Space (Jürgen Friedrichs & Jörg Blasius) -- Chapter 6. The Social Space of mid-20th Century University Teachers in Sweden – The Case of Human Sciences (Tobias Dalberg) -- Chapter 7. Nation-States as Fields (Andreas Schmitz, Daniel Witte & Heiko Heiberger) -- Chapter 8. Capital Portfolios and Reproduction Strategies. Constructing the Social Space Based on Household Panel Data (Olaf Groh-Samberg & Nora Waitkus) -- Chapter 9. Five Ways to Apprehend Classes (Stine Thidemann Faber, Annick Prieur, Lennart Rosenlund & Jakob Skjøtt-Larsen) -- Chapter 10. Cultural Domains and Class Structure: Assessing Homologies and Cultural Legitimacy (Nicolas Robette & Olivier Roueff) -- Chapter 11. The French Political Space after the Terror Attacks of Paris (Jean Ciché) -- Chapter 12. Intergenerational Reproduction of Transnational and National Cultural Capital (Martin Munk) -- Chapter 13. The Social Space of Norway (Magne Flemmen & Lennart Rosenlund) -- PART II: Modeling Social Fields -- Chapter 14. The University within Academic Capitalism (Richard Münch) -- Chapter 15. Economy in Crisis – Crisis of Economics? (Christian Schmidt-Wellenburg) -- Chapter 16. Mapping the Public of a Literary Festival with MCA: the Specificity of Literary Capital (Myrtille Picaud, Jérôme Pacouret & Gisèle Sapiro) -- Chapter 17. Transformations of the Danish Field of Welfare Work – Shifting Forms of Dominated Capital (Jan Thorhauge Frederiksen) -- Chapter 18. Social Field and Market: How Social Groups Use Education in Times of Privatization (Håkan Forsberg, Mikael Palme & Mikael Börjesson) -- Chapter 19. Investigating the Social Space of a Professional Group: the Case of Nursing (Michael Gemperle) -- PART III: Methodology and Methods -- Chapter 20. Analyzing Evolutions from Barometer Data Using Correspondence Analysis after Data Doubling and Cluster Analysis: Application to the French “Barometer of Political Trust”(Brigitte Le Roux & Frédrik Cassor) -- Chapter 21. The Geometry and Topology of Data and Information for Analytics of Processes and Behaviours: Building on Bourdieu and Addressing New Societal Challenges (Fionn Murtagh) -- Chapter 22. Class-Specific Analysis. Methodological and Sociological Reflections (Frederic Lebaron & Philippe Bonnet) -- Chapter 23. A Holistic and Modeling Framework to Analyze the Structure of Social Space (Ivaylo Petev) -- Chapter 24. Biographical Illusion? Rethinking the Role of Biographical Research in Bourdieusian Social Theory (Ciaran Burke & Delyth Edwards) -- Chapter 25. Establishing Correspondence Analysis in Sociology Training in the German Speaking Academia (Rainer Diaz-Bone & Katharina Manderscheid) -- Chapter 26. Homology Hypothesis in France, Norway and Switzerland: Actuality of the Question and Methodological Challenges (Dominique Joye, Gunn Elisabeth Birkelund & Yannick Lemel) -- Chapter 27. Using Geometric Data Analysis to construct International Spaces: The Case of “IB World Schools” (Leonora Dugonjic) -- Chapter 28. Qualitative Methodology of Habitus Construction (Heinrich Schäfer, Leif Seibert & Adrian Tovar).